Ecological economics : sustainability in practice - Shmelev, Stanislav E. (Springer, 2012)
In a concise and crisp manner, this book presents the state of the art in ecological economics, an interdisciplinary field focused on the analysis of sustainability of global, national and regional economic systems. An elegant guide, the book offers a range of cutting edge methods used in sustainability research including multicriteria decision aid (MCDA), input-output analysis, and life cycle analysis. This book is packed with references for students with some background in economics, environmental science or mathematics who aim to develop the analytical skills required for redirecting our de